Akibat Hukum Perkawinan Campuran di Indonesia dalam Perspektif Hukum Perdata Internasional: Kewarganegaraan Anak dan Waris - Nia Noviyani; Sigit Wibowo (Jurnal Hukum Caraka Justitia, 2026)
These mixed marriages have resulted in increased cross-border interactions, giving rise to various legal issues, particularly regarding children's citizenship and inheritance rights. Differences in citizenship principles and legal systems between countries have the potential to create legal openness for children from mixed marriages. The main focus of this study is to analyze the legal consequences of mixed marriages in Indonesia from the perspective of international civil law, particularly regarding the citizenship status of children and their position as heirs. The research methodology applied is normative juridical with a statutory and conceptual approach through a literature review. An interesting finding is that Law Number 12 of 2006 concerning Citizenship has not been fully optimal in providing legal protection through the recognition of limited dual citizenship for children from mixed marriages, but there is still potential for conflict in determining the child's personal status. Furthermore, differences in citizenship do not eliminate children's rights as heirs, although their implementation is limited by certain legal provisions. This study emphasizes the need for regulatory harmonization to ensure legal certainty and equitable protection of children's rights.